Homogeneous casting method for metal alloy / nano-carbon composite material with high diversion and high plasticity

By adopting non-contact high-speed stirring and negative pressure directional solidification technology in metal alloys, uniform dispersion of nanocarbon is achieved, and the problems of uneven dispersion of nanocarbons and high flow diversion and high plasticity in the prior art are solved, and the ingot quality and processing performance of composite materials are improved.

CN119753390AActive Publication Date: 2025-04-04CENT SOUTH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411945200.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The prior art is difficult to achieve uniform dispersion of nanocarbons and high flow diversion and high plasticity in metal alloys and nanocarbon composites, resulting in poor metallurgical quality and poor processing performance of composite materials.

Method used

The non-contact high-speed continuous stirring technology is used to realize the in-situ interface reaction between nanocarbon and alloying elements in the metal melt, and combined with negative pressure and directional solidification technology to form a homogeneous ingot.

Benefits of technology

The uniform and random dispersion of nanocarbon in metal alloys is achieved, forming a high flow diversion network, taking into account high flow diversion and high plasticity, and improving the ingot metallurgy quality and subsequent processing performance of composite materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753390A_ABST
    Figure CN119753390A_ABST
Patent Text Reader

Abstract

The invention discloses a homogeneous casting method for a metal alloy / nanocarbon composite material with both high diversion and high plasticity, and belongs to the technical field of composite material preparation. Comprising the following steps: heating to melt matrix metal, adding specific alloying elements to obtain a master alloy melt, adding a carbon material to the surface of the melt at a temperature at which the reaction power of the carbon material and the alloying elements is enough, and rolling the carbon material into the high-temperature melt by a high-speed vortex formed by stirring, the elements react with defect sites of a carbon material at high temperature to obtain carbides, so that metal-covalent heterojunctions are formed in the in-situ reaction process of a high-temperature melt, after alloying elements in the melt fully react with the carbon material, vacuumizing is performed to achieve negative pressure while the stirring effect is kept, directional solidification is performed upwards from the bottom, and the metal-covalent heterojunctions are formed. And cooling to form the metal alloy / carbon composite material homogeneous cast ingot with high diversion and high plasticity. The adopted preparation method is simple, the casting speed is high, and the cost is low.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite material preparation, and relates to a homogeneous casting method of a metal alloy / nano-carbon composite material with both high conductivity and high plasticity. Background Art

[0002] As we all know, nanocarbon materials with special crystal configurations (such as graphene, carbon nanotubes, carbon fibers, etc.) have extremely high conductivity and heat conductivity, and their theoretical conductivity performance is even much greater than that of metal materials. However, this special crystal configuration also determines that it does not have the same processability as metal materials. Metal materials exhibit excellent plasticity due to the non-directional nature of metal bonds. At the same time, the presence of a large number of free electrons also brings good conductivity. Combining metal alloys with nanocarbon is expected to take into account both high conductivity and high plasticity, and obtain ultra-high conductivity composite materials that can be processed and deformed. However, there are many difficulties in the composite of the two: the interface between metal and nanocarbon is not very friendly, the density difference is large in most cases, nanocarbon is difficult to disperse in metal, and the ingot metallurgical quality of the composite material is poor.

[0003] At present, the methods for compounding metal materials with nanocarbon are mainly divided into two categories: solid-state method (represented by powder metallurgy) and liquid method (represented by traditional contact stirring casting). Among them, the powder metallurgy process (such as CN112779481A) has the disadvantages of temperature not being higher than the melting point, insufficient interface reaction, long process, high cost and low efficiency. The prepared metal alloy / carbon composite material has poor performance and cannot take into account high conductivity and high plasticity. The traditional contact stirring casting process has many disadvantages such as insufficient uniformity, poor effect with increasing viscosity, difficulty in coordinating directional solidification, easy pollution and high requirements for stirring paddle materials, and cannot achieve uniform dispersion of nanocarbon in the metal matrix. Patent CN110724887A discloses a method for reinforcing aluminum-based composite materials by coupling in-situ self-generated TiC particles with carbon fibers. Continuous carbon fibers are clamped by a clamp to react in the melt, and then the continuous carbon fibers are dispersed by ultrasonic vibration and mechanical stirring. Although the dispersion effect of the continuous carbon fibers is improved, what is ultimately obtained is only a directional continuous fiber composite material (as can be seen in conjunction with the attached drawings). The continuous fibers penetrate the matrix metal and do not achieve true uniform random dispersion. The subsequent deformation processing is prone to cause interface rupture, and the subsequent processing performance is poor. In addition, it is mainly used to improve shear resistance, and does not mention the high conductivity that is of concern in this article. Summary of the invention

[0004] In view of the above shortcomings, the present invention proposes a homogeneous casting method for a metal alloy / nanocarbon composite material with both high conductivity and high plasticity. The main principle is: to achieve sufficient in-situ interface reaction between elements in the metal melt and nanocarbon under non-contact high-speed continuous stirring, and then combine negative pressure and directional solidification technology to obtain a homogeneous ingot with good metallurgical quality. The preparation method adopted by the present invention is simple, has a fast casting speed and low cost.

[0005] The technical solution of the present invention is as follows:

[0006] A homogeneous casting method for a metal alloy / nano-carbon composite material having both high conductivity and high plasticity is provided, comprising the following steps:

[0007] (1) melting a base metal, adding specific alloying elements to obtain a master alloy melt, and stirring the master alloy melt in a non-contact high-speed stirring environment to cause the master alloy melt to flow at a high speed to form a disordered turbulent flow;

[0008] (2) preparing nanocarbon, adding the nanocarbon to the surface of the master alloy melt at a stirring temperature at which the nanocarbon and the specific alloying element have sufficient reaction power, and using the large and small vortices in the disordered turbulence to draw the nanocarbon on the surface into the master alloy melt, so that the specific alloying element reacts with the defect sites of the nanocarbon to obtain carbides, forming a metal-covalent heterojunction, improving the interface affinity between the nanocarbon and the melt, and promoting the uniform and random dispersion of the nanocarbon under non-contact high-speed stirring;

[0009] (3) while continuing to maintain the stirring effect, vacuum is drawn to achieve negative pressure, and directional solidification is performed from the bottom upward, which can not only gradually discharge the gas involved in the melt from bottom to top, but also maintain the dispersion effect in the ingot, and the nano-carbon exceeding the critical content is interconnected in the matrix metal to form a flow-conducting network, thereby forming a homogeneous ingot of the metal alloy / nano-carbon composite material;

[0010] (4) The homogeneous ingot of the metal alloy / nano-carbon composite material is subjected to hot and cold working deformation. Since the nano-carbon is uniformly and randomly dispersed in the matrix metal, the nano-carbon and the matrix metal can achieve a coordinated effect during the deformation process, so the processing plasticity is good, thereby obtaining a metal alloy / nano-carbon composite material with both high conductivity and high plasticity.

[0011] Furthermore, the nanocarbon has a discontinuous nanostructure.

[0012] Furthermore, the specific alloying element refers to an alloying element that is slightly excessive and easily combines with carbon to form stable carbides, has a certain solid solubility in the matrix metal melt, and is easily de-melted from the matrix metal when the temperature is lowered.

[0013] Furthermore, the homogeneous ingot of the metal alloy / nano-carbon composite material in step (3) is a non-directionally arranged nano-carbon composite material.

[0014] Furthermore, the base metal is one of copper Cu, aluminum Al, iron Fe, magnesium Mg, titanium Ti, zinc Zn, lithium Li or an alloy thereof.

[0015] Furthermore, the specific alloying element is one or more of chromium Cr, zirconium Zr, silicon Si, titanium Ti, molybdenum Mo, manganese Mn, and boron B.

[0016] Furthermore, the specific alloying element is added in the form of a master alloy.

[0017] Furthermore, in step (2), the stirring temperature is selected to be 100 degrees Celsius higher than the melting point of the master alloy to ensure the fluidity of the melt. To ensure the reaction kinetics of the carbon material and the alloying elements, the stirring temperature is not less than 800 degrees Celsius, the stirring speed is greater than 300 rpm, and the volume fraction of the nanocarbon is controlled between 0.1-30%.

[0018] Furthermore, in step (2), the stirring temperature is selected between 1000-1800 degrees Celsius, the stirring speed is greater than 800 rpm, and the volume fraction of the nanocarbon is controlled between 1-10%.

[0019] Furthermore, in the step (3), the vacuum pumping speed is greater than 5 L / min to ensure that the gas involved in the melt is released under negative pressure, thereby avoiding the occurrence of pores and looseness during the directional solidification process; the temperature gradient of directional solidification is greater than 5 degrees Celsius / mm to refine the cast grain size and ensure that the nanocarbon is evenly distributed in the ingot.

[0020] Compared with the prior art, the beneficial technical effects of the present invention are:

[0021] (1) During the casting process, the intrinsic structure of the nanocarbon will not be destroyed, thereby maintaining the high conductivity properties to the maximum extent. The interface reaction between the nanocarbon and the metal matrix is ​​sufficient, and the nanocarbon is evenly dispersed in the ingot, which can efficiently form a conductivity network.

[0022] (2) The obtained homogeneous ingot has small interface flow resistance and high bonding strength, and can still maintain a high bonding force during the subsequent plastic deformation process, thereby taking into account both processing capability and high flow conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the morphology of the original powder of the carbon fiber described in the present invention.

[0024] Figure 2This is the cast structure of the copper alloy / carbon fiber composite material in Example 1 of the present invention.

[0025] Figure 3 This is the hot-rolled structure of the copper alloy / carbon fiber composite material in Example 1 of the present invention.

[0026] Figure 4 This is the cast structure of the copper alloy / carbon fiber composite material in Example 3 of the present invention.

[0027] Figure 5 This is a morphology diagram of the original carbon nanotube powder described in the present invention.

[0028] Figure 6 This is a morphology diagram of the original graphene powder described in the present invention.

[0029] Figure 7 This is the cast structure of the aluminum alloy / carbon fiber / carbon nanotube / graphene composite material in Example 3 of the present invention.

[0030] Figure 8 This is the cast structure of the magnesium-lithium alloy / carbon fiber composite material in Example 4 of the present invention. DETAILED DESCRIPTION

[0031] The technical solutions in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0032] Example 1

[0033] The embodiment of the present invention provides a homogeneous casting method of a copper alloy / carbon fiber composite material having both high conductivity and high plasticity, comprising the following steps:

[0034] (1) melting pure Cu, CuCr master alloy, and CuZr master alloy at a high temperature of 1800 degrees Celsius to obtain a Cu-0.5Cr-1Zr master alloy melt;

[0035] (2) Lower the melt temperature to 1400 degrees Celsius and add 5 vol.% carbon fiber (such as Figure 1 As shown, the average diameter of the carbon fiber is 10 microns, the length is 200 microns, the intrinsic thermal conductivity is 1200 W / (m·K)), and the stirring speed is 1000 rpm;

[0036] (3) After the Cr and Zr in the melt fully react with the carbon fiber, while maintaining the stirring effect, vacuum is drawn to achieve a negative pressure of 0.1 Pa, and directional solidification is carried out from the bottom to the top. The temperature gradient of the directional solidification is 30 degrees Celsius / mm. After cooling, the required copper alloy / carbon fiber composite material homogeneous ingot is formed (cast structure such as Figure 2 The ingot was subjected to a hot rolling test at 900 degrees Celsius with a deformation of 75% (the longitudinal section SEM image is shown in Figure 3 As shown) and the ingot was subjected to a cold rolling test with a 75% deformation, and after cold rolling, a stress relief annealing was performed at 300 degrees Celsius for 5 hours.

[0037] Comparative sample 1: The same process is used without adding alloying elements Cr and Zr.

[0038] Comparative sample 2: The same process is used without adding the alloying element Zr.

[0039] Comparative sample 3: using the same process, the stirring speed is lower than 200 rpm.

[0040] Comparative sample 4: Using the same process, normal pressure replaces negative pressure.

[0041] Comparative sample 5: Using the same process, casting is used instead of directional solidification.

[0042] Its performance data is shown in Table 1.

[0043] Table 1 Performance data of copper carbon fiber composite material in Example 1

[0044]

[0045] Analysis of results: There is no alloying element in Comparative Example 1, which cannot change the incompatibility between copper and carbon. Under the same process conditions, the content of carbon material entering into and dispersing in the copper melt is very limited, and the ingot is close to pure copper. In Comparative Example 2, only the alloying element Cr is added, and a chromium carbide excess can be formed on the surface of the carbon fiber, which has a certain effect, but the performance is not as good as the combined addition of Cr and Zr. In Comparative Example 3, the stirring speed is low, and the melt mainly flows horizontally rather than turbulently. The stirring and dispersion effects are limited and the effect is not good. In Comparative Sample 4, normal pressure is used instead of negative pressure, and the gas involved in the ingot is not easy to discharge, and the performance is reduced. In Comparative Sample 5, casting is used instead of directional solidification. After casting, the melt cannot maintain the stirring effect, the carbon material floats to a certain extent, and the performance of the ingot is reduced.

[0046] Example 2

[0047] The embodiment of the present invention provides a homogeneous casting method of a copper alloy / carbon fiber composite material having both high conductivity and high plasticity, comprising the following steps:

[0048] (1) melting pure Cu, CuCr master alloy, and CuZr master alloy at a high temperature of 1800 degrees Celsius to obtain a Cu-1Cr-2Zr master alloy melt;

[0049] (2) lowering the melt temperature to 1500°C, adding 10 vol.% carbon fiber (the average diameter of the carbon fiber is 10 μm and the length is 200 μm), and stirring at a speed of 2500 rpm;

[0050] (3) After the Cr and Zr in the melt fully react with the carbon fiber, while maintaining the stirring effect, vacuum is drawn to achieve a negative pressure of 0.1 Pa, and directional solidification is carried out from the bottom to the top. The temperature gradient of the directional solidification is 30 degrees Celsius / mm. After cooling, the required copper alloy / carbon fiber composite material homogeneous ingot (such as Figure 4 The ingot was subjected to a hot rolling test at 900 degrees Celsius with a deformation amount of 75%, and a cold rolling test at 75% deformation amount. After the cold rolling, stress relief annealing was performed at 300 degrees Celsius for 5 hours.

[0051] Its performance data is shown in Table 2.

[0052] Table 2 Performance data of copper carbon fiber composite material in Example 2

[0053]

[0054] Example 3

[0055] The present invention provides a homogeneous casting method for an aluminum alloy / carbon fiber / carbon nanotube / graphene composite material having both high conductivity and high plasticity, comprising the following steps:

[0056] (1) melting 5005 aluminum alloy and AlSi master alloy at a high temperature of 1500 degrees Celsius to obtain a 5005Al-1Si master alloy melt;

[0057] (2) Add 5 vol.% carbon fiber (the average diameter of the carbon fiber is 10 μm and the length is 200 μm), 1 vol.% carbon nanotube (such as Figure 5 As shown, the average diameter of carbon nanotubes is 200 nanometers and the length is 20 micrometers) and 0.3 vol.% of graphene (as shown Figure 6 As shown, the average graphene diameter is 10 microns), the stirring speed is 1500 rpm, a high-speed vortex is formed in the melt, and the melt stirs and disperses the carbon fiber, carbon nanotubes and graphene in the form of turbulence;

[0058] (3) After the Si in the melt fully reacts with the carbon material, while maintaining the stirring effect, vacuum is drawn to achieve a negative pressure of 0.1 Pa, and directional solidification is performed from the bottom to the top. The temperature gradient of the directional solidification is 20 degrees Celsius / mm. After cooling, the required 5005Al-Si / carbon fiber / carbon nanotube / graphene composite homogeneous ingot (such as Figure 7 The ingot was subjected to a hot rolling test at 450 degrees Celsius with a deformation amount of 75%, and a cold rolling test at 75% deformation amount. After the cold rolling, stress relief annealing was performed at 200 degrees Celsius for 5 hours.

[0059] Its performance data is shown in Table 3.

[0060] Table 3 Performance data of aluminum-carbon composite material in Example 3

[0061]

[0062] Example 4

[0063] The present invention provides a homogeneous casting method for a magnesium-lithium alloy / carbon composite material having both high conductivity and high plasticity, comprising the following steps:

[0064] (1) melting the Mg-10Li alloy and the MgZr master alloy at a high temperature of 1200 degrees Celsius to obtain a Mg-10Li-1Zr master alloy melt;

[0065] (2) adding 5 vol.% carbon fiber (the average diameter of the carbon fiber is 10 μm and the length is 200 μm) and stirring at a speed of 2000 rpm to form a high-speed vortex in the melt, and the melt stirs and disperses the carbon fiber in the form of turbulence;

[0066] (3) After the Zr in the melt fully reacts with the carbon material, the stirring effect is maintained while vacuuming to achieve a negative pressure of 0.1 Pa, and directional solidification is performed from the bottom to the top. The temperature gradient of the directional solidification is 20 degrees Celsius / mm. After cooling, the desired MgLiZr / carbon fiber composite material homogeneous ingot (such as Figure 8 The ingot was subjected to a hot rolling test at 400 degrees Celsius with a deformation amount of 75%, and a cold rolling test at 75% deformation amount. After the cold rolling, stress relief annealing was performed at 200 degrees Celsius for 5 hours.

[0067] Its performance data is shown in Table 4.

[0068] Table 4 Performance data of magnesium-lithium-carbon composite material in Example 4

[0069]

[0070] The embodiments of the present invention are described in detail, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions and variations made to these embodiments without departing from the principles and spirit of the present invention still fall within the protection scope of the present invention.

Claims

1. A homogeneous casting method for a metal alloy / nano-carbon composite material having both high conductivity and high plasticity, characterized in that: The following steps are involved: (1) melting a base metal, adding specific alloying elements to obtain a master alloy melt, and stirring the master alloy melt in a non-contact high-speed stirring environment to cause the master alloy melt to flow at a high speed to form a disordered turbulent flow; (2) preparing nanocarbon, adding the nanocarbon to the surface of the master alloy melt at a stirring temperature at which the nanocarbon and the specific alloying element have sufficient reaction power, and using the large and small vortices in the disordered turbulence to draw the nanocarbon on the surface into the master alloy melt, so that the specific alloying element reacts with the defect sites of the nanocarbon to obtain carbides, forming a metal-covalent heterojunction, improving the interface affinity between the nanocarbon and the melt, and promoting the uniform and random dispersion of the nanocarbon under non-contact high-speed stirring; (3) while continuing to maintain the stirring effect, vacuum is drawn to achieve negative pressure, and directional solidification is performed from the bottom upward, which can not only gradually discharge the gas involved in the melt from bottom to top, but also maintain the dispersion effect in the ingot, and the nano-carbon exceeding the critical content is interconnected in the matrix metal to form a flow-conducting network, thereby forming a homogeneous ingot of the metal alloy / nano-carbon composite material; (4) The homogeneous ingot of the metal alloy / nano-carbon composite material is subjected to hot and cold working deformation. Since the nano-carbon is uniformly and randomly dispersed in the matrix metal, the nano-carbon and the matrix metal can achieve a coordinated effect during the deformation process, so the processing plasticity is good, thereby obtaining a metal alloy / nano-carbon composite material with both high conductivity and high plasticity.

2. A homogeneous casting method for a metal alloy / nano-carbon composite material having both high conductivity and high plasticity according to claim 1, characterized in that: The nanocarbon has a discontinuous nanostructure.

3. The homogeneous casting method of a metal alloy / nano-carbon composite material having both high conductivity and high plasticity according to claim 1, characterized in that: The specific alloying element refers to an element that is slightly excessive and easily combines with carbon to form a stable carbide, has a certain solid solubility in the matrix metal melt, and is easily de-melted from the matrix metal when the temperature is lowered.

4. The homogeneous casting method of the metal alloy / nano-carbon composite material having both high conductivity and high plasticity according to claim 2, characterized in that: The homogeneous ingot of the metal alloy / nano-carbon composite material in step (3) is a non-directionally arranged nano-carbon composite material.

5. A homogeneous casting method for a metal alloy / nano-carbon composite material having both high conductivity and high plasticity according to claim 1, characterized in that: The base metal is one of copper Cu, aluminum Al, iron Fe, magnesium Mg, titanium Ti, zinc Zn, lithium Li or an alloy thereof.

6. A homogeneous casting method for a metal alloy / nano-carbon composite material having both high conductivity and high plasticity according to claim 3, characterized in that: The specific alloying elements are one or more of chromium Cr, zirconium Zr, silicon Si, titanium Ti, molybdenum Mo, manganese Mn, and boron B.

7. A homogeneous casting method for a metal alloy / nano-carbon composite material having both high conductivity and high plasticity according to claim 6, characterized in that: The specific alloying elements are added in the form of a master alloy.

8. A homogeneous casting method for a metal alloy / nano-carbon composite material having both high conductivity and high plasticity according to claim 1, characterized in that: In the step (2), the stirring temperature is selected to be 100 degrees Celsius higher than the melting point of the master alloy to ensure the fluidity of the melt. To ensure the reaction kinetics of the carbon material and the alloying elements, the stirring temperature is not less than 800 degrees Celsius and the stirring speed is greater than 300 rpm. The volume fraction of the nanocarbon is controlled between 0.1-30%.

9. A homogeneous casting method for a metal alloy / nano-carbon composite material having both high conductivity and high plasticity according to claim 1, characterized in that: In the step (2), the stirring temperature is selected between 1000-1800 degrees Celsius, the stirring speed is greater than 800 rpm, and the volume fraction of the nanocarbon is controlled between 1-10%.

10. A homogeneous casting method for a metal alloy / nano-carbon composite material having both high conductivity and high plasticity according to claim 1, characterized in that: In the step (3), the vacuum pumping speed is greater than 5 L / min to ensure that the gas involved in the melt is released under negative pressure to avoid the occurrence of pores and looseness during the directional solidification process; the temperature gradient of directional solidification is greater than 5 degrees Celsius / mm to refine the cast grain size and ensure that the nanocarbon is evenly distributed in the ingot.

Citation Information

Patent Citations

  • Method for in-situ synthesis TiC particle and carbon fiber coupling reinforced aluminum matrix composite

    CN110724887A

  • Method for preparing carbon fiber reinforced aluminum-based composite material through solvent dispersion and freeze drying

    CN112779481A

  • Metal-matrix bionic composite material reinforced by carbon nanomaterials, and preparation method thereof

    CN108994301A

  • Method for strengthening magnesium matrix composites through carbon nanomaterials of different type structures

    CN109182820A

  • Method for manufacturing nanocarbon-metal composite material

    CN1869262A